Main chemical constituents and mechanism of anti‐tumor action of Solanum nigrum L - Zhen‐duo Zhao; Cheng Hu; Ling Li; Jia‐qi Zhang; Li‐chao Zhang (Cancer Medicine)
Abstract Objective Solanum nigrum L. (SNL) is a natural drugwith diverse bioactive components and multi‐targeted anti‐tumor effects, gaining increasing attention in clinical application. Method and Results This paper reviews the studies on SNL by searching academic databases (Google Scholar, PubMed, Science Direct,and Web of Science, among others), analyzing its chemical compositions (alkaloids, saponins, polysaccharides, and polyphenols, among others), andbriefly describes the anti‐tumor mechanisms of the main components. Discussion This paper discusses the shortcomings of the current research on SNL and proposes corresponding solutions, providing theoretical support for further research on its biological functions and clinical efficacy.